Analysis of correlations between psychological factors and self-reported behavior of motorcyclists in Malaysia, depending on self-reported usage of different types of motorcycle facility. (April 2017) - Sukor, Nur Sabahiah Abdul; Tarigan, Ari K.M.; Fujii, Satoshi
Highlights: The study investigates correlations between psychological factors and self-reported behavior of motorcyclists, depending on self-reported usage of different types of motorcycle facilities. The study shows that the exclusive road lanes' usage correlates with the speeding behavior. The psychological factors were found to influence the self-reported risky behaviors. Abstract: Segregated road lanes for motorcyclists are one of the practices implemented by the Malaysian authority to decrease the number of road crashes involving motorcycles. In this study, the motorcycle lanes are divided into three types, exclusive, inclusive, and paved shoulder. This study examined the correlations between motorcyclists' psychological factors and their risky riding behaviors (speeding and neglecting to wear helmet), depending on self-reported usage of different types of motorcycle facilities. The psychological factors discussed in this study were: attitude, desire, perceived behavior control, moral obligation, perceived danger, fear of being caught, and perception of others' behaviors toward the risky behaviors. Quantitative analyses, including Structural Equation Modeling, were used as the analytical tools. The results demonstrated the statistically significant relationship of exclusive road lanes' usage on speeding behavior. However, no statistically significant correlation was found for segregated lanes' usage on helmet wearing behavior. Psychological factors were found affecting the motorcyclists' likelihood of performing the risky behaviors. However, these factors influence speeding and helmet wearing behavior differently. The study offers recommendations and theoretical contributions to explain the complex relationships among the uses of segregated lanes, riders' psychological factors, and their risky behaviors.